The Effect of Integration in A Dance Instruction Model for Undergraduate Students in General Education at Rajamangala University of Technology - et. al., Sangworn Jankorn, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research aimed to study the effect of Integration in a Dance Instruction Model for undergraduate students in General Education at Rajamangala University of Technology. The research methodology was the Quasi Experimental Research and Evaluation Research with Mixed Research Method. Conduct teaching and learning according to the Integration in a Dance Instruction Model. The sample group in the research was undergraduate students of Rajamangala University of Technology Thanyaburi Who are enrolled in dance In general education courses, semester 1, academic year 2019, 2 groups, which were obtained by selecting a specific A total of 60 people, divided into 30 people each. The data were analyzed by content analysis, analytic induction, basic statistics, One-Way Sample t-test and a One-Way ANCOVA. Research findings. The study was found that the dance skills of students were higher than before the study at a statistically significant level of .05. The students who studied with the Integration in Dance Instruction Model had better dance skills than the other dance students at a statistically significant level of .05. The students studied with the Integration in Dance Instruction Model with different instructors, and the results were found to be similar. The students who studied with the Integration in Dance Instruction Model had higher satisfaction levels at the most level and higher than the other participants.